2015
DOI: 10.1161/atvbaha.114.305089
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Integrin β3 Delays Endothelial Cell Regeneration and Contributes to Arteriovenous Graft Failure in Mice

Abstract: Objective Neointima formation is associated with stenosis and subsequent thrombosis in arteriovenous grafts (AVG). A role of integrin β3 in the neointima formation of AVGs remains poorly understood. Approach and Results In integrin β3−/− mice, we found significantly accelerated occlusion of AVGs compared to the wild type mice. This is caused by the development of neointima and lack of endothelial regeneration. The latter is a direct consequence of impaired functions of circulating angiogenic cells (CACs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…These results showed that the ECs of AVFs from ESRD patients express the mesenchymal cell marker, SMA-α. We also reported that integrin β3 expression was located in the endothelium and neointima of arteriovenous grafts from patients [10]. Double staining of SMA-α and integrin β3 in AVFs from mice and patients confirmed that SMA-α and integrin β3 were located in the endothelium and the neointima (Fig.…”
Section: Integrin β3 Expression In Avfssupporting
confidence: 63%
See 2 more Smart Citations
“…These results showed that the ECs of AVFs from ESRD patients express the mesenchymal cell marker, SMA-α. We also reported that integrin β3 expression was located in the endothelium and neointima of arteriovenous grafts from patients [10]. Double staining of SMA-α and integrin β3 in AVFs from mice and patients confirmed that SMA-α and integrin β3 were located in the endothelium and the neointima (Fig.…”
Section: Integrin β3 Expression In Avfssupporting
confidence: 63%
“…Circulating endothelial progenitor cells deficient in integrin β3 show impaired adhesion activity toward exposed subendothelium, fail to differentiate into mature ECs, and promote neointimal formation at arteriovenous graft sites [10]. However, integrin αvβ3 arginine-glycine-aspartic acid (RGD) antagonists have been used to reduce neointimal hyperplasia, mainly by blocking VSMC accumulation [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies support the emerging concept that Notch signaling is also involved in the development of neointimal hyperplasia. The increased Notch-1 signaling mediates neointimal formation in integrin β3(−/−)-induced arteriovenous graft occlusion through impairing EC regeneration [ 19 ]. Dll-4-mediated Notch activation promotes VSMC proliferation and migration in vein graft lesions and leads to vein graft failure [ 20 , 21 ].…”
Section: The Notch Signaling Pathwaymentioning
confidence: 99%
“…As shown in Figure 2 , Notch activation suppresses EC proliferation, regeneration and promotes neointimal formation ( Figure 2 A). In integrin β3 knockout mice, the increased Notch-1 signaling inhibits circulating angiogenic cells’ (CACs) homing and differentiation, delays endothelial regeneration and promotes neointimal formation at the sites of arteriovenous grafts [ 19 ]. It is also reported that endothelial progenitor cells’ (EPCs) activity is greater in Notch-1(+/−) EPCs than in wild type (WT) EPCs, and subsequently, transplantation of Notch-1(+/−) bone marrow accelerates endothelial recovery after arterial injury in WT mice.…”
Section: Endothelial Cell Proliferation and Regenerationmentioning
confidence: 99%